2005
DOI: 10.1007/s00415-005-0857-1
|View full text |Cite
|
Sign up to set email alerts
|

The combination of cyclophosphamide plus interferon beta as rescue therapy could be used to treat relapsing–remitting multiple sclerosis patients

Abstract: The aim of the present study was to evaluate the efficacy of the combination of cyclophosphamide (CTX) and interferon beta (IFN beta) in a group of relapsing remitting (RR) multiple sclerosis (MS) patients who experienced treatment failure during IFN beta therapy. It is the general experience that immunomodulatory agents (IMA) are only partially effective in RR patients. Recent data on the efficacy of immunosuppressive therapies for these patients are encouraging. The anti-inflammatory and immunosuppressive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Cyclophosphamide is typically infused monthly (with or without induction) and works as an immunosuppressing agent affecting cytokine expression (with pronounced effects on IL-12) along with T-cell and B-cell function [95]. In adults with RRMS, cyclophosphamide appears to reduce relapse rate and the accrual of new lesions on MRI [96,97] Fig. 2 Proposed algorithm for the approach to treating a pediatric patient with multiple sclerosis (MS) [40].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Cyclophosphamide is typically infused monthly (with or without induction) and works as an immunosuppressing agent affecting cytokine expression (with pronounced effects on IL-12) along with T-cell and B-cell function [95]. In adults with RRMS, cyclophosphamide appears to reduce relapse rate and the accrual of new lesions on MRI [96,97] Fig. 2 Proposed algorithm for the approach to treating a pediatric patient with multiple sclerosis (MS) [40].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…It is generally administered as monthly maintenance therapy, in some cases preceded by an induction course. Cyclophosphamide has been shown to be effective in relapse rate reduction 1,2 and in control of MRI lesion accrual 1,3 ; however, effects in delaying disease progression have been variable. [4][5][6][7] Several studies have suggested that cyclophosphamide treatment may be most beneficial in younger adult patients, [7][8][9] and in patients with early secondary progressive MS. 6,7,10 MS onset before the age of 18 years is estimated at 2.7%-10.5% [11][12][13] of all patients.…”
mentioning
confidence: 99%
“…Monotherapy use of Mito or Cy [15,[19][20][21][22][23][24] or either used in combination with immunomodulatory agents [25][26][27] has considerably increased over the last years. Despite the risk of dramatic adverse events, like severe acute or delayed heart failure [28] and acute myeloid leukaemia [20][21][22][23][24][25][26][27][28][29][30], Mito has become, after approval by the FDA and EMEA, a first-line rescue therapy for RRMS patients who do not respond to IMA and for rapidly deteriorating SPMS [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the risk of dramatic adverse events, like severe acute or delayed heart failure [28] and acute myeloid leukaemia [20][21][22][23][24][25][26][27][28][29][30], Mito has become, after approval by the FDA and EMEA, a first-line rescue therapy for RRMS patients who do not respond to IMA and for rapidly deteriorating SPMS [31][32][33][34]. Cy, although used in many MS Centres in Europe and the US [35], is not approved for MS and can be used in Italy only when informed consent is obtained.…”
Section: Discussionmentioning
confidence: 99%